Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa di SMA Negeri 1 Bojongmanik - Ratiah, Ratiah; Lindawati, Yustika Irfani (Lembaga Yasin AlSys, 2022)
This study aims to 1). Knowing how the teacher's strategy in increasing student motivation at SMAN 1 Bojongmanik, 2). To find out what factors or obstacles are often found when motivating students so that these students are motivated to continue learning. This research is a descriptive qualitative research with a case study approach, the participation of this research is 3 teachers of SMAN 1 Bojongmanik. This research uses data collection methods in the form of observation, interviews and documentation. The results of the study show that the teacher's role is a very important role in increasing student learning motivation, such as always reminding students to stay enthusiastic when studying, appreciating active students, inviting less active students to interact in class, and helping students who do not understand, and not blaming students who try to answer even though the answer is wrong, and using new and not monotonous learning media, for example showing learning videos, using quiziz and google form affiliations and giving rewards to students who get the highest score.